Role of Rewards and Recognition Programs on Employee Motivation and Performance in Nepalese Commercial Bank - Chand, Manisha (Nepalese Journal of Management, 2025)
The study examines the role of reward and recognition program on employee motivation and performance in Nepalese commercial banks. Employee motivation and employee performance are selected as dependent variables. The selected independent variables are salary, bonus, fringe benefit, recognition and promotion. The primary source of data is used to assess the opinions of respondents regarding salary, bonus, fringe benefit, recognition, promotion, employee motivation and employee performance of employees towards rewards and recognition programs in Nepalese commercial bank. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and role of rewards and recognition programs on employee motivation and performance in Nepalese commercial bank. The study showed that salary is positively correlated to employee motivation and employee performance. It indicates that higher the salary, higher would be the employee motivation and employee performance. Similarly, bonus is positively correlated to employee motivation and employee performance. It indicates that bonus leads to increase in employee motivation and employee performance. Likewise, fringe benefit is positively correlated to employee motivation and employee performance. It indicates that higher the fringe benefit, higher would be the employee motivation and employee performance. Further, recognition is also positively correlated to employee motivation and employee performance. It indicates that higher the recognition, higher would be the employee motivation and employee performance. In addition, promotion is positively correlated to employee motivation and employee performance. It indicates that good promotion leads to increase in employee motivation and employee performance.